Serine‐227 in the N‐terminal kinase domain of RSK2 is a potential therapeutic target for mantle cell lymphoma. (18th May 2020) - Matsumura‐Kimoto, Yayoi; Tsukamoto, Taku; Shimura, Yuji; Chinen, Yoshiaki; Tanba, Kazuna; Kuwahara‐Ota, Saeko; Fujibayashi, Yuto; Nishiyama, Daichi; Isa, Reiko; Yamaguchi, Junko; Kawaji‐Kanayama, Yuka; Kobayashi, Tsutomu; et al.
Abstract: RSK2 is a serine/threonine kinase downstream signaling mediator in the RAS/ERK signaling pathway and may be a therapeutic target in mantle cell lymphoma (MCL), an almost incurable disease subtype of non‐Hodgkin lymphoma. In this study, serine‐227 (RSK2 Ser227 ) in the N‐terminal kinase domain (NTKD) of RSK2 was found to be ubiquitously active in five MCL‐derived cell lines and in tumor tissues derived from five MCL patients. BI‐D1870, an inhibitor specific to RSK2‐NTKD, caused RSK2 Ser227 dephosphorylation, and thereby, induced dose‐dependent growth inhibition via G2 /M cell cycle blockade and apoptosis in four of the five cell lines, while one cell line showed only modest sensitivity. In addition, RSK2 gene knockdown caused growth inhibition in the four BI‐D1870‐sensitive cell lines. Comparative gene expression profiling of the MCL‐derived cell lines showed that inhibition of RSK2 Ser227 by BI‐D1870 caused downregulation of oncogenes, such as c‐MYC and MYB; anti‐apoptosis genes, such as BCL2 and BCL2L1; genes for B cell development, including IKZF1, IKZF3, and PAX5; and genes constituting the B cell receptor signaling pathway, such as CD19, CD79B, and BLNK. These findings show that targeting of RSK2 Ser227 enables concomitant blockade of pathways that are critically important in B cell tumorigenesis. In addition, we found favorable combinatory growth inhibitory effects of BI‐D1870 with inhibitors of BTK (ibrutinib), AKT (ipatasertib), and BCL2 (venetoclax) in cell characteristic‐dependent manners. These results provide a rationale for RSK2 Ser227 in the NTKD as a potential therapeutic target in MCL and for future development of a novel bioavailable RSK2 NTKD‐specific inhibitor. Abstract : RSK2Ser227 in the N‐terminal kinase domain (NTKD) of RSK2 was found to be ubiquitously active in mantle cell lymphoma (MCL). RSK2 concomitantly regulates series of genes involved in oncogenesis, apoptosis, B cell development, and B cell receptor signaling. RSK2Ser227 in the NTKD is a potential therapeutic target in MCL.